Comparison of Therapeutic Effects of Topical Application of Diclofenac Sodium Nanoparticles and Conventional Placebo on Knee Osteoarthritis: Diclofenac Sodium Nanoparticles and Conventional Placebo - Li, Taotao; Guo, Mingbo; Zhang, Wenlong (Cellular and Molecular Biology, 2022)
The objective of this study was to investigate the therapeutic effects of diclofenac sodium nanoparticles and traditional placebo on Knee Osteoarthritis (KOA). 80 KOA patients admitted to the Inpatient Department of Orthopedics of Sunshine Union Hospital from June 2020 to July 2021 were selected, and divided into 40 cases using diclofenac sodium nano flexible liposomes topically (study group) and 40 cases using conventional placebo topically (control group). The two groups were compared for knee swelling, knee pain, and knee function scores before treatment, on the 3rd, 7th, and 14th days after treatment, and the incidence of adverse events during treatment was recorded. It was found that the knee swelling scores of the study group were significantly lower than those of the control group on the 7th and 14th days after treatment, and that the knee pain score of the study group was significantly lower than that of the control group at the 7th day after treatment, and that the knee joint mobility disorder scores of the study group were significantly lower than those of the control group at the 7th and 14th days after treatment. The total effective rate of the study group was 85.0% (34/30), which was higher than that of the control group (12.5% (5/30)) (P<0.05). In conclusion, local application of diclofenac sodium nano flexible liposomes showed a stronger effect on KOA than traditional placebo, and no significant adverse reactions occurred.